New challenges for eLearning : supporting learning content through semantic web technology - Hazalina Hashim (2009)
Nowadays, the web has become an important learning platform. Its accessibility has made it a successful environment particularly for eLearning education. However, the emerging technology of the Semantic Web sets out challenges that need to be explored in bringing the eLearning platform to the next level. This paper discusses the potential of semantic technology for supporting learning content in the eLearning environment. A conceptual model is referred to present the idea of learning content development through semantic web technology in the educational context. Furthermore, the ontological development model describes the process involved in building concepts and ontologies from learning content. Lastly, this paper also explains the impacts of semantic technology that contribute to the changes of a longer-term aim of eLearning education. (Author's abstract)